Simulasi Efektivitas Model Berbagai Peredam Kebisingan (Studi Kasus : Kawasan Zona Bising di Kota Kendari) - Djalante, Susanti; Nurrakhmad Arsyad, La Ode Muhamad; Sugiarto, Try; Putra, Adris Ade (JOURNAL TEKNIK SIPIL DAN INFRASTRUKTUR, 2015)
The rapid economic activity in Kendari is followed by a rapid increase in traffic volume. This leads to one of consequence that increased noise levels and air pollution in Kendari, especially in zone which has a relatively high trip attraction. The purposes of this study are to analyze the effectiveness or insertion loss (IL) of various kinds/types of noise barriers. This research was conducted in some zones which have different types of noise barriers, different elevation or embankment barrier in the education zone, glass material barrier in the trade zone, concrete building barrier in the office zone, and combination different elevation and plant barrier in the hospital zone. The method used in the study is the Practical Method using a sound level meter, then is calculated by using Insertion Loss (IL ) equation, and Empirical Methods used the equation in the "Calculation of Road Noise Level". This research shows comparing various barriers in the noise zone that in various distances, 10,17,13 and 10 m, the type of glass barrier in in the trade zone has the highest effectiveness level or insertion loss of 16.9 dB, followed by concrete building barrier at 14 dB in the office zone. While, the level of effectiveness/insertion loss of different elevation/embankment in the education and the combination of plants and elevation/embankment barrier in the hospital zone was almost the same value about of 6.9 dB and 5.98 dB. At the same distance (10 m) of each zone, the glass was still higher levels of effectiveness of 12.25 dB, followed by concrete building barrier in 11,02 dB, by combination elevation and plants of 6.15 dB, and the type of elevation/embankment 6.05 dB. Thus, the types of barrier provide varying influence on the value of the effectiveness/insertion loss, and to improve the effectiveness /insertion loss of various barriers can be combined with distance change.